COMPARISON OF KETOROLAC VERSUS DICLOFENAC AS TREATMENT FOR ACUTE RENAL COLIC: A SYSTEMATIC REVIEW AND A NETWORK META-ANALYSIS (DIRECT AND INDIRECT COMPARISON) - Arianto, Eko; Rodjani, Arry; Wahyudi, Irfan (Indonesian Journal of Urology, 2021)
Objective: The purpose of this study is to compare which analgesic is better between ketorolac and diclofenac. Material & Methods: A systematic search was conducted in Pubmed, Science Direct, Cochrane, EBSCO, Proquest database, and PICO analysis was used in determining the study question. The included article in the analysis was randomized controlled trials. Results: A total of 6 articles were included in the analysis, with no significant differences between ketorolac and diclofenac both in a direct comparison and indirect comparison (OR 2.74 [95%CI 0.72 – 10.43]; p= 0.14 and OR 0.51 [95%CI 0.29 – 0.91]; p= 0.49). Conclusion: Both ketorolac and diclofenac have the same efficacy in treating renal colic.